Gambaran Risiko Ide Bunuh Diri pada Mahasiswa Fakultas Kedokteran Universitas Andalas - Taufik Ashal (Majalah Kedokteran Andalas, 2022)
Introduction: Suicidal ideation is defined as the thought of injuring or killing oneself. This is an important factor for predicting suicide attempts and is considered an index of other mental health problems.  Objective: This study aims to identify risk of suicidal ideation of medical students in faculty of medicine, Andalas University. Method: This is a descriptive study by assessing risk of suicidal ideation using the Risk Factors of Suicidal Ideation (RFSI) questionnaire. Total sampling technique was used in medical students’ class of 2021 and 2022 of the Andalas University. Result:  Four hundred and ninety six medical students was included in this study. Loneliness is a dimension of risk of suicidal ideation that experienced by 22.2% of medical students. There were 125 (25.2%) medical students who had risk of suicidal ideation. There were 16,1% of female students and 9,1% male students that had risk of suicidal ideation. Conclusion: Loneliness is the dimension that mostly experienced by medical students with risk of suicidal ideation. The number of female medical students who have risk of suicidal ideation is higher than men. Two classes were found to have a similar percentage of students with risk of suicidal ideation.